Low Incomes in Agriculture in OECD Countries - Yasuhiko Kurashige; Bong Hwan Cho (Luxembourg Income Study (LIS), 2001)
This study examines low income in agriculture. It uses microeconomic data and provides an analysis of the incidence of low incomes in farm households compared to other households. Social security policies as they affect agricultural households are described and the impact of taxes and transfers are examined for both farm and non-farm households by comparing incomes before and after tax and social transfers.
Keywords: 330; Agrareinkommen; Armut; Niedrigeinkommen; Sozialpolitik; OECD-Staaten